Doctor‐patient relationship: Evidence from Bangladesh. Issue 4 (1st October 2021) - Hamid, Syed Abdul; Begum, Afroza; Azim, Md. Ragaul; Islam, Md. Sirajul
Abstract: Background and Aims: This study analyses the nature and magnitude of the doctor‐patient relationship in Bangladesh, intending to trigger policy discussions for improving healthcare quality. The dearth of research on the nature and degree of this relationship in Bangladesh as well as the global context motivates us to conduct this study. Method: We use primary data from three different surveys conducted during July to October 2018. The study conducts a public perception survey on 701 individuals at various public places in Dhaka City. In addition, we interview 100 exit‐patients from two major public hospitals, four for‐profit‐private hospitals, and one not‐for‐profit private hospital in Dhaka City. We also interview a total of 62 doctors of different ladders. Each survey uses a structured questionnaire with a set of questions customized in the Bangladesh context. Results: The score of the doctor‐patient relationship is found quite low from the viewpoint of the public, the patients, and the doctors. However, the score is comparatively high from the doctor's point of view. The results show that lack of optimum time allocation for the patients, not explaining the prescription clearly, and discriminating the patients by their social status are the main factors for a poor relationship with doctors. Conclusions: The doctor‐patient relationship is substantially poor from the public, patients, and the doctors' viewpoints. Orienting the doctors to non‐therapeutic care (ie, respectful behavior, privacy, dignity, prompt attention, clear communication) in all levels of medical education and training, and improving working conditions of the hospitals are the crucial policy implications.